The Influence Of Workload, Work Stress And Social Support On Job Performance In Seafarers: Mediated By Work Motivation - Eko Hadi Suyanto; Hwihanus , Hwihanus (Jurnal Scientia, 2024)
This research aims to examine the influence of workload, work stress, and social support on job performance in seafarers, with work motivation as a mediating variable. The seafaring profession has a high level of challenge and risk, which can cause significant workload and job stress, and affect job performance. Social support from family, friends, or coworkers can help reduce work stress and increase work motivation. This research used a survey method with a questionnaire distributed to 100 sailors in the city of Banjarmasin. Data analysis was carried out using SmartPLS 3.2.9 software with non-probability sampling methods and purposive sampling techniques. The research results show that workload and work stress have a positive and significant effect on job performance. Social support also has a positive effect on job performance. In addition, work motivation mediates the relationship between workload, work stress, social support, and job performance. This research confirms the importance of social support and work motivation in improving the job performance of seafarers who work in environments with high workload and stress.